ANALISIS PENGARUH DEBIT AIR TERHADAP KINERJA PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) MENGGUNAKAN 4 BUAH SUDU - Jupriyanto Sihaloho (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2021)
Micro hydro power plant (PLTMH), is a small-scale power plant that uses hydropower as its driving force, such as irrigation canals, rivers or natural waterfalls by utilizing the head and the amount of water discharge. The purpose of this study was to determine how the effect of water discharge on the performance of a whirlpool turbine type micro hydro power plant and how much power was produced by a whirlpool turbine type micro hydro power plant. The process in this study was carried out by analyzing the performance of a micro hydro power plant consisting of tube volume, water discharge, water power, turbine power generator power, torque and turbine efficiency. The results of this study are the best potential for water discharge produced by a micro hydro power plant of the whirlpool turbine type prototype is in the third experiment with a discharge of 0.00625 m³/s with a turbine power of 0.54 Watt and a power generated by a generator 10, 53 Watts. The efficiency of the whirlpool turbine prototype micro hydro power plant was also obtained in the third experiment with a turbine efficiency value of 3.8%. Micro hydro power plants are very influential on the height of the fall of water into the turbine, the higher the fall of water, the greater the power generated.